Electro-explosive iron powders as a catalyst of synthesis liquid hydrocarbons from CO and H2 in Fischer-Tropsch process; Petroleum and Coal; Vol. 58, iss. 7 - Popok E. V. Evgeniy Vladimirovich; Levashova A. I. Albina Ivanovna; Gladchenko T. M. Tatjyana Mikhaylovna; Burlutsky N. P. Nikita Pavlovich; Zhuravkov S. P. Sergey Petrovich (2016, 2016)
Title screen